Cytophagic histiocytic panniculitis: Report of two cases - Jayasree Manoj; Feroze Kaliyadan; Manoj Unni; A D Dharmaratnam (Wolters Kluwer Medknow Publications, 2011)
Cytophagic histiocytic panniculitis (CHP) was first described in 1980 by Winkelmann as a chronic histiocytic disease of the subcutaneous adipose tissue, which is characterized clinically by tender erythematous nodules, recurrent high fever, malaise, jaundice, organomegaly, serosal effusions, pancytopenia, hepatic dysfunction, and coagulatory abnormalities. CHP may occur either isolated or as part of cutaneous manifestations of hemophagocytic syndrome. Here, we report two different presentations of CHP.